The Effect of Different Feedback on Writing Quality of College Students with Different Cognitive Styles - Wahyuni, Sri (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Feedback provision in the process of writing has been believed that it is beneficial. However, different strategies of providing feedback may affect differently on writing quality of students. This study aimed at investigating the effect of different feedback provision on the writing quality of students having different cognitive styles. By conducting an experimental through a factorial research design, fifty-five of the fourth semester English students of STAIN Kediri were involved in this study. For analyzing the data, a two-way ANOVA was employed. The findings revealed that the effect of different feedback on writing quality of the students does not depend on the students’ cognitive styles. The result of the main effect analysis revealed that there was no significant difference on writing quality of students getting direct corrective feedback and those getting indirect corrective feedback.